The Effect of performance based evaulation on preservice biology teachers’ achievement and laboratory report writing skills - Güneş, Perihan; Katırcıoğlu, Hikmet; Yılmaz, Mirac (Journal of Turkish Science Education, 2015)
The aim of this study is to determine the effect of performance based evulation on preservice biology teachers’ cognitive achievements and laboratory report writing skills about DNA isolation. In the study, nonequivalent control-group design were used to determine the effect of performance based evaluation on pre-service biology teachers’ achievement and laboratory report skills about DNA isolation. The sample of the study was 70 pre-service teachers. A rubric and DNA isolation achievement test were developed for the data collection. Data was collected by pre-and post-administration of achievement test and administration of rubric. Before the beginning of the study, a pre-test was applied in order to determine the cognitive field levels of students on DNA isolation. Then, a DNA isolation test was applied to the experiment and control groups. While the experiment group was given a rubric to be used during writing their laboratory reports, the control group was not. At the end of the study, a post-test was applied in order to determine students’ cognitive field levels. To detect the differences between the experimental and the control groups, the independent samples t-test was used. At the end of the study, it was determined that preservice teachers who use rubrics display a higher skill in writing laboratory reports and have a higher cognitive field level compared to those who do not.